HUBUNGAN PERAN IBU DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN KEJADIAN KARIES GIGI PADA MURID KELAS II DI SD NEGERI 62 BANDA ACEH - Reca, Reca; Nuraskin, Cut Aja; Rosmini, Rosmini (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
School age children are an important age in the process of growth and development. Elementary school age children are children aged 6-12 years. Dental and oral health problems are problems that are often experienced by the elementary school age group, so they require vigilance and good and correct dental care. The role of the mother has an influence on the level of dental and oral health in children, because the mother is someone who is able to understand and can provide understanding in maintaining oral health. Based on the initial data of the examination conducted on 10 second grade students at SD Negeri 62 Banda Aceh, it was found that from 10 students, 90% of students had dental caries. This research was conducted by analytical method. With a cross sectional design. Data collection was obtained through interviews and examination of dental caries status. The sample in this study used a total sampling technique, which amounted to 31 respondents. Bivariate analysis used chi-square statistical test with 0.05. The results showed that of the 31 respondents the role of the mother as a motivator was not good as many as 21 people (67.7%), 19 people were less good educators (61.3%), and 20 people were less than good facilitators (64.5%). The results of the chi-square statistical test obtained the value of the mother's role as a motivator (p value 0.015), educator (p value 0.012), and facilitator (p value 0.029). It can be concluded that there is a relationship between the mother's role in maintaining oral health and the incidence of dental caries in second grade students at SD Negeri 62 Banda Aceh. It is suggested to the students to increase their attention in preventing dental caries, provide dental and oral health needs such as toothbrush, fluoride toothpaste, and teach children how to brush their teeth properly and correctly.